A cross-sectional study of burnout and its associations with learning environment and learner factors among psychiatry residents within a National Psychiatry Residency Programme. Issue 8 (August 2019) - Chew, Qian Hui; Ang, Lye Poh; Tan, Lay Ling; Chan, Herng Nieng; Ong, Seh Hong; Cheng, Ambrose; Lai, Yew Min; Tan, Ming Yee; Tor, Phern Chern; Gwee, Kok Peng; Sim, Kang
Abstract : Background: Multiple studies have reported high burnout rates among residents, including psychiatry. There is a paucity of studies examining the relationship between burnout and learning context, stress levels, resilience, stigma in healthcare providers and coping methods concurrently within the same cohort. Objective: We examined the rate of burnout among our psychiatry residents in a cross-sectional study and hypothesised that burnout is associated with poorer perception of learning environment, greater perceived stress, stigma levels, lower resilience and specific coping strategies during training. Methods: Ninety-three out of 104 psychiatry residents (89.4%) within our National Psychiatry Residency Programme participated in the study from June 2016 to June 2018. Relevant scales were administered to assess the perception of learning environment, burnout, stress, resilience, stigma levels and coping methods, respectively. We performed comparisons of the above measures between groups (burnout vs no burnout) and within-group correlations for these same measures. Results: Overall, 54.8% of the sample met criteria for burnout. Residents with burnout had poorer perception of the learning environment, greater stress levels (both p<0.001), were less willing to disclose/seek help and employed greater active-avoidance coping strategies. Within the burnout group, greater perceived stress was correlated with poorer perception of learning environment (rs =−0.549) and greater use of active-avoidance coping (rs =0.450) versus additional use of problem-focussed coping within the non-burnout group. Conclusions: Burnout was related to both environment and learner factors. These findings viewed within the transactional, sequential and imbalance models of burnout suggest the need to address stressors, beef up coping, provide continual support and develop resilience among our learners.